(untitled) (Tạp chí Y học Cộng đồng, 2025)
Objective: This study aimed to describe the prevalence of anxiety disorders among patients with cardiovascular diseases in Soc Son District, Hanoi, in 2023. Methods: A cross-sectional study was conducted on 418 patients diagnosed with cardiovascular diseases who attended seven commune health stations in Soc Son District from June to July 2023. Anxiety symptoms were assessed using the DASS-21 scale. Results: The prevalence of anxiety symptoms was 32.1%, with 35.1% classified as mild, 44.8% moderate, 14.9% severe, and 5.2% extremely severe. Common physical manifestations included dry mouth (11.5%), noticeable heartbeat (9.8%), and excessive sweating (9.6%). Conclusion: Anxiety disorders are common among patients with cardiovascular diseases at the primary healthcare level. Early screening and appropriate interventions are crucial for improving treatment outcomes and enhancing patients’ quality of life.